Visit of Prime Minister Dr. Manmohan Singh to South Africa, September 30 - October 03, 2006 - Manmohan Singh 1932- (Public Diplomacy Division, Ministry of External Affairs, Government of India, 2006)
Transcript of speeches delivered during his South Africa visit.